Phylogenomics of Plant-Associated Botryosphaeriaceae Species - Garcia, Jadran F.; Lawrence, Daniel P.; Morales-Cruz, Abraham; Travadon, Renaud; Minio, Andrea; Hernandez-Martinez, Rufina; Rolshausen, Philippe E.; Baumgartner, Kendra; Cantu, Dario (Frontiers in Microbiology, 2021)
The Botryosphaeriaceae is a fungal family that includes many destructive vascular pathogens of woody plants (e.g., Botryosphaeria dieback of grape, Panicle blight of pistachio). Species in the genera Botryosphaeria, Diplodia, Dothiorella, Lasiodiplodia, Neofusicoccum, and Neoscytalidium attack a range of horticultural crops, but they vary in virulence and in their abilities to infect their hosts via different infection courts (flowers, green shoots, woody twigs). Isolates of seventeen species, originating from symptomatic apricot, grape, pistachio, and walnut were tested for pathogenicity to grapevine wood after four months of incubation in potted plants in the greenhouse. Results revealed significant variation in virulence in terms of the length of the internal wood lesions caused by these seventeen species. Phylogenomic comparisons of the seventeen species of wood-colonizing fungi revealed clade-specific expansion of gene families representing putative virulence factors involved in toxin production and mobilization, wood degradation, and nutrient uptake. Statistical analyses of the evolution of the size of gene families revealed expansions of secondary metabolism and transporter gene families in Lasiodiplodia and of secreted cell wall degrading enzymes (CAZymes) in Botryosphaeria and Neofusicoccum genomes. In contrast, Diplodia, Dothiorella, and Neoscytalidium generally showed a contraction in the number of members of these gene families. Overall, species with expansions of gene families, such as secreted CAZymes, secondary metabolism, and transporters, were the most virulent (i.e., were associated with the largest lesions), based on our pathogenicity tests and published reports. This study represents the first comparative phylogenomic investigation into the evolution of possible virulence factors from diverse, cosmopolitan members of the Botryosphaeriaceae.